Reformulasi Bangun Sistem Ekonomi Islam - Elly Masykuroh (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2011)
The idea of this paper came from the many phenomenas of economic problem occuring in various part of the world that become increasingly serious. Both economis school of capitalist and socialist was not able to provide solution for the increasingly complex economic issues. This condition raises expectation for an alternative economic system that is able to resolve economic problem. Current discourses about Islamic economic system sound relevance and begin to be studied to resolve the economic problem. Through the study and reconstruction of the history of Islamic economy, it shows that system of Islamic economy does exist legally and de facto. Now, our job is to formulate the form and concept of Islamic economy that can be accepted as an alternative economic system in the world. The formulation of the concept and theory of Islamic economy can take two alternatives: firstly, through revision of the old theory of Islamic economy in accordance with the principle and characteristic of Islamic economy, secondly, the recontruction of history through the Islamic economic thought, so that it can gave birth new Islamic economic system.